Why the Crackling Deformations of Single Crystals, Metallic Glasses, Rock, Granular Materials, and the Earth's Crust Are So Surprisingly Similar - Dahmen, Karin A.; Uhl, Jonathan T.; Wright, Wendelin J. (Frontiers in Physics, 2019)
Recent experiments show that the deformation properties of a wide range of solid materials are surprisingly similar. When slowly pushed, they deform via intermittent slips, similar to earthquakes. The statistics of these slips agree across vastly different structures and scales. A simple analytical model explains why this is the case. The model also predicts which statistical quantities are independent of the microscopic details (i.e., they are “universal”), and which ones are not. The model provides physical intuition for the deformation mechanism and new ways to organize experimental data. It also shows how to transfer results from one scale to another. The model predictions agree with experiments. The results are expected to be relevant for failure prediction, hazard prevention, and the design of next-generation materials.